2019
DOI: 10.1097/j.pain.0000000000001508
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive biases in pain: an integrated functional–contextual framework

Abstract: Cognitive biases in the context of pain.Contemporary models explaining the exacerbation and maintenance of pain, disability and distress, assign a pivotal role to cognitive biases. These models assume that cognitive biases are maladaptive, trait-like processes, and propose that individuals who selectively attend to pain-related information (attention bias), interpret ambiguous pain and/or health relevant information as threatening (interpretation bias), and/or recall pain-related information selectively or as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 89 publications
4
67
1
Order By: Relevance
“…Given the nature of the disease and its treatment, cancer‐related pain may be associated with significant distress, feelings of uncertainty, and threatening thoughts of mortality . Cognitive‐affective models of pain posit that these factors would have a powerful, lasting influence on how CCS experience and interpret pain in their everyday lives . Yet, there is a limited understanding of how having cancer shapes children's meaning of pain after treatment has ended.…”
Section: Introductionmentioning
confidence: 99%
“…Given the nature of the disease and its treatment, cancer‐related pain may be associated with significant distress, feelings of uncertainty, and threatening thoughts of mortality . Cognitive‐affective models of pain posit that these factors would have a powerful, lasting influence on how CCS experience and interpret pain in their everyday lives . Yet, there is a limited understanding of how having cancer shapes children's meaning of pain after treatment has ended.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the present study did not find the significant effect of pain catastrophizing on attentional patterns to pain stimuli, we found pain catastrophizing plays a role for psychological health and life adjustment for the chronic pain patients. Results of the present study may stress the importance of investigating the interplay among attention, interpretation and psychological factors such as pain catastrophizing because cognitive bias to pain-related information can be adaptive or maladaptive depending on contexts (Van Ryckeghem et al, 2019).…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, they may not react sensitively to pain stimuli and interpret pain stimuli as threatening in the same manner as chronic pain patients with musculoskeletal disorders. So, for those individuals, interpreting ambiguous bodily sensations as threatening and catastrophizing during the early stage of attention can determine attentional engagement to those stimuli during the later stage of attention (Van Ryckeghem et al, 2019). Future studies need to compare attentional and interpretational biases between chronic pain patients with different types of chronic pain conditions (e.g., musculoskeletal disorders vs. autoimmune diseases) and compare attentional biases toward different types of stimuli including ambiguous sensorimotor stimuli, pictures of body part relevant to the pain location as well as symbolic pain stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently suggested that a generalized cognitive inflexibility impacts the way chronic pain patients attend to, interpret and recollect information; processes often referred to collectively as executive functioning (Van Ryckeghem et al, 2019). Executive functions (EF) is an umbrella term that describes mental processes regulating our behavior, especially in non-routine situations (Diamond, 2013;Goldstein and Naglieri, 2014;Friedman and Miyake, 2017).…”
Section: Introductionmentioning
confidence: 99%